Late Quaternary climate change in Australia's arid interior: Evidence from Kati Thanda – Lake Eyre. (15th September 2022) - Cohen, Tim J.; Arnold, Lee J.; Gázquez, Fernando; May, Jan-Hendrik; Marx, Sam K.; Jankowski, Nathan R.; Chivas, Allan R.; Garćia, Adriana; Cadd, Haidee; Parker, Adrian G.; Jansen, John D.; Fu, Xiao; et al.
Abstract: Williams Point is an iconic late Quaternary sedimentary sequence exposed at the southern margin of Madigan Gulf at Kati Thanda – Lake Eyre (KT-LE), Australia's largest lake. The ∼15 m high cliff outcrop includes 6 m of aeolian sediments, capping a ∼0.5 m beach/shoreline facies containing abundant Coxiella (aquatic gastropod) unconformably overlying 5–6 m of fluvio-lacustrine facies. The base of the outcrop and the playa floor comprises shallow and deeper water laminated lacustrine sediments. We re-examine the stratigraphic sequence using detailed excavations, micromorphological analysis and geochemical characterisation (X-ray fluorescence, X-ray diffraction, palaeoecology, stable isotope analysis of gypsum hydration water and biogenic carbonates, rare earth element analysis) and present a revised chronology using single-grain optically stimulated luminescence (OSL) within a Bayesian framework. Our new chronostratigraphic data generally supports previous interpretations for Williams Point, but crucially refines the timing of several of the key sedimentological units. The deeper-water lacustrine facies on the lake floor, unconformably overlying the Miocene Etadunna Formation, were deposited 206 ± 13 ka (232–169 ka, 95% credible interval; C.I.). A palaeoplaya, or oxidised shallow lake deposits, formed at 153 ± 11 ka (175–131 ka, 95% C.I.) and the uppermost shallow water lacustrine facies at the base of the cliff was deposited at 131 ± 9 ka (150–113 ka, 95% C.I.). An unconformity separates these sediments from the overlying fluvio-lacustrine phase, securely constrained (with eight OSL samples) to 86 ± 4 ka (95–78 ka, 95% C.I.). The isotopic composition of the palaeo-lake water (δ 18 O and δD), reconstructed from the hydration water of syndepositional gypsum formed in-situ in these fluvio-lacustrine sediments, indicates wetter conditions at 95–78 ka than at ca. 232–131 ka. Based on the provenance analysis these fluvio-lacustrine and lacustrine sediments were sourced from the northern catchments within the Lake Eyre basin but with an additional contribution from the northern Flinders Ranges. An erosional unconformity separates this sedimentary unit from the overlying Coxiella beach facies, which itself dates to 71 ± 4 ka (79–63 ka; 95% C.I.). This beach facies is interpreted to represent a regressional shoreline or near-shore deposit formed during Marine Isotope Stage [MIS] 4. This is the most reliable palaeolake level indicator in the sequence and indicates a maximum water depth of 12 m. The overlying Williams Point aeolian unit (WPAU) dates to 49 ± 4 ka (56–41 ka, 95% C.I.), slightly younger than previous estimates. The modelled age for WPAU overlaps with (and is within uncertainty of) the last KT-LE megalake phase, which reached +5 m AHD at 48 ± 2 ka. However, considering its elevation (−3 to +3 m AHD), the age of this gypsiferous aeolian unit demands that it accreted as KT-LE was entering a playa phase with lengthy periods of exposed lake floor. In turn, this means that the putative Genyornis newtoni (a megafaunal flightless bird) which laid its eggs in the gypsiferous dunes, went extinct during a time of hydrological transformation. These results bring fresh perspectives to a site that has held a heavy sway over previous views of the Quaternary history of Australia's arid zone. Highlights: Williams Point, at Kati Thanda- Lake Eyre shows episodic sedimentation in a lacustrine setting from 230 to 131 ka and fluvio-lacustrine deposition at 86 ka. Coxiella beach facies were deposited at 71 ka, showing water depths of 12 m. Rare earth elements show northern catchments supplied water and discharge in MIS 7–4. Gypsiferous aeolian sedimentation occurred at 49 ka contemporaneously with the last mega lake highstand. Genyornis newtoni (a megafaunal flightless bird) went extinct during a time of hydrological transformation.